Legal providing of aerospace industry activity of Ukraine: the state and perfection prospects - Бєглий, Олександр Васильович; Боярська, Зоя Іванівна; Єряшов, Євген Кузьмович (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2012)
In article it is analyzesed new aspects of legal regulation of the state and civil aviation by mechanisms ofan air law of Ukraine.